Modulation of neuroinflammation by natural plant compounds: a promising approach for ischemic stroke - Niu, Pingping; Zhang, Yonggang; Wang, Binghao; Qiu, Sheng; Dong, Quanming; Li, Liqin; Li, Yuntao (Frontiers in Pharmacology, 2025)
Ischemic stroke remains a leading global cause of mortality and long-term disability, imposing substantial health and economic burdens on society. Although interventions such as intravenous thrombolysis and mechanical thrombectomy have proven effective, their narrow therapeutic time window restricts accessibility for many patients. Post-ischemic brain injury is significantly driven by a cascade involving inflammatory cells and mediators, culminating in an “inflammatory storm” that damages neuronal cells. Consequently, targeting neuroinflammation following ischemic stroke to explore potential therapeutic strategies is of paramount importance. Natural plant compounds, bioactive constituents derived from plants, demonstrate considerable promise for ischemic stroke treatment, with many exhibiting potent neuroinflammation-modulating activities. This review synthesizes current research on natural plant compounds targeting post-ischemic stroke neuroinflammation and elucidates their underlying mechanisms of action. It aims to offer insights for developing plant-derived therapeutics specifically targeting neuroinflammation after ischemic stroke.